Determinants of capital structure: evidences from Bursa Malaysia / Muhd Haziq Mahali - Mahali, Muhd Haziq (2017)
This study has aimed to investigate the determinants of capital structure for oil and gas listed companies listed in Bursa Malaysia. The data recovered from 20 oil and gas companies over the period 2010 to 2016. The data has been run in the Stata12 with use panel data since it is the appropriate model. The independent variables used in this study are profitability, liquidity and tangibility while the dependent variable is leverage. The data is gathered from secondary data which are DataStream and annual report of the listed companies. The main finding in this study indicates that the profitability has positive significant while liquidity has negative significant relationship to the leverage. Then, tangibility does not affect the leverage which is insignificant relationship. This finding has been supported by the capital structure theory and several previous researchers.